2018
DOI: 10.1111/jphp.13020
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential ofMusaspp. inflorescence: a systematic review

Abstract: Objectives Extracts of parts Musa spp. have been used for the treatment of various diseases in traditional medicine. Studies have shown that these extracts have hypoglycaemic properties. The aim of this work was to gather evidence on the antidiabetic effects of Musa spp. inflorescence. Methods A systematic review was conducted with searches in three electronic databases, along with manual searches. Studies evaluating the antidiabetic properties of extracts of flower or bract of the genus Musa (in vitro or in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It has been reported in the literature that Musa species have antioxidant and antidiabetic potential, especially the inflorescence part, friut, and the flowers samples (Adedayo, Oboh, Oyeleye, & Olasehinde, 2016;Kalita et al, 2016). Vilhena et al (2018) found 16 studies reporting the antidiabetic property of the inflorescence (flowers and bract) of Musa spp., which all supported the ethnomedicinal claim that cooked flowers are able to treat diabetes mellitus. Some other extensive reviews have been compiled on the bioactive compounds from fruit, sap, and peel of banana (Pothavorn et al, 2010;Singh et al, 2016;Tsamo et al, 2015).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…It has been reported in the literature that Musa species have antioxidant and antidiabetic potential, especially the inflorescence part, friut, and the flowers samples (Adedayo, Oboh, Oyeleye, & Olasehinde, 2016;Kalita et al, 2016). Vilhena et al (2018) found 16 studies reporting the antidiabetic property of the inflorescence (flowers and bract) of Musa spp., which all supported the ethnomedicinal claim that cooked flowers are able to treat diabetes mellitus. Some other extensive reviews have been compiled on the bioactive compounds from fruit, sap, and peel of banana (Pothavorn et al, 2010;Singh et al, 2016;Tsamo et al, 2015).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…diabetic activity of extracts from banana flowers or inflorescence toward the inhibition of -glucosidase and -amylase enzyme, inhibition of diabetes in animals, or stimulation of glucose uptake in muscle cells[6][7][8][9].Together, those findings illustrate the health benefits of banana flowers and inflorescence.Musa (ABB group) Namwa Mali-Ong is an edible banana that belongs to the ABB banana cultivar group. This cultivar is well-known throughout Thailand as Thai people utilize all parts of the tree.…”
mentioning
confidence: 99%
“…The inflorescence of this banana is mainly used as a vegetable in many Thai dishes. Although many investigations have shown an anti-diabetic activity of banana inflorescence[6][7][8][9], the anti-diabetic activity of Musa (ABB group) Namwa Mali-Ong inflorescence has not been illustrated. Therefore, this study used an ethanolic extract of the entire inflorescence from Musa (ABB group) Namwa Mali-Ong to analyze its anti-diabetic activity.…”
mentioning
confidence: 99%